If this one is 180 degrees with one die being (4n+22) and the other being (8n-10) Which equation can be used to determine the value of these two adjacent angles?
(1 point)
Responses
(4n + 22) + (8n - 10) = 90
(4n + 22) + (8n - 10) = 90
(4n + 22) + (8n - 10) = 180
(4n + 22) + (8n - 10) = 180
(4n + 22) - (8n - 10) = 180
(4n + 22) - (8n - 10) = 180
4n + 22 = 8n - 10
11 answers
(4n + 22) + (8n - 10) = 180
Determine the value of n in the angle pair above.
If this one is 180 degrees with one die being (4n+22) and the other being (8n-10)
(1 point)
Responses
n =12
n =12
n = 14
n = 14
n = 148
n = 148
n = 168
If this one is 180 degrees with one die being (4n+22) and the other being (8n-10)
(1 point)
Responses
n =12
n =12
n = 14
n = 14
n = 148
n = 148
n = 168
n = 14
How is it n=14 can you explain it?
Sure, to determine the value of n, we combine the two expressions that represent the angles:
Angle 1: 4n + 22
Angle 2: 8n - 10
Since these angles are adjacent and add up to 180 degrees, we sum them:
(4n + 22) + (8n - 10) = 180
4n + 22 + 8n - 10 = 180 (Combine like terms)
12n + 12 = 180 (Simplify further)
12n = 168 (Subtract 12 from both sides)
n = 168 / 12
n = 14
Therefore, n = 14 is the solution.
Angle 1: 4n + 22
Angle 2: 8n - 10
Since these angles are adjacent and add up to 180 degrees, we sum them:
(4n + 22) + (8n - 10) = 180
4n + 22 + 8n - 10 = 180 (Combine like terms)
12n + 12 = 180 (Simplify further)
12n = 168 (Subtract 12 from both sides)
n = 168 / 12
n = 14
Therefore, n = 14 is the solution.
Arthur is playing in his room, which is 24.3 feet above ground. He then descends 39.9 feet to the basement, where his uncle is working in his workshop. If ground zero is 0 feet, which number best describes the location of the basement woodshop?
(1 point)
Responses
-64.2 feet
-64.2 feet
-15.6 feet
-15.6 feet
15.6 feet
15.6 feet
64.2 feet
(1 point)
Responses
-64.2 feet
-64.2 feet
-15.6 feet
-15.6 feet
15.6 feet
15.6 feet
64.2 feet
-15.6 feet
To find the location of the basement woodshop, we need to determine the elevation from ground zero. When Arthur descends, he moves downwards. Since ground zero is 0 feet (on the ground level), and if the room's elevation is 24.3 feet above ground (a positive number), descending 39.9 feet would take him lower than ground zero.
The calculation would be:
Elevation at room - Elevation of Descend = Elevation of Basement
24.3 feet - 39.9 feet = -15.6 feet
Therefore, the location of the basement woodshop is -15.6 feet below ground zero.
To find the location of the basement woodshop, we need to determine the elevation from ground zero. When Arthur descends, he moves downwards. Since ground zero is 0 feet (on the ground level), and if the room's elevation is 24.3 feet above ground (a positive number), descending 39.9 feet would take him lower than ground zero.
The calculation would be:
Elevation at room - Elevation of Descend = Elevation of Basement
24.3 feet - 39.9 feet = -15.6 feet
Therefore, the location of the basement woodshop is -15.6 feet below ground zero.
Of the cars in a used-car lot, 2/5
are the color gray. 2/3
of the gray cars are electrically powered vehicles. What fraction of the cars on the lot are both gray and electrically powered?
(1 point)
Responses
1/15
1 over 15
2/15
2 over 15
4/15
4 over 15
1/2
are the color gray. 2/3
of the gray cars are electrically powered vehicles. What fraction of the cars on the lot are both gray and electrically powered?
(1 point)
Responses
1/15
1 over 15
2/15
2 over 15
4/15
4 over 15
1/2
To find the fraction of cars on the lot that are both gray and electrically powered, we need to multiply the fraction of cars that are gray by the fraction of gray cars that are electrically powered.
Fraction of cars that are gray: 2/5
Fraction of gray cars that are electrically powered: 2/3
(2/5) * (2/3) = 4/15
Therefore, 4/15 of the cars on the lot are both gray and electrically powered.
Fraction of cars that are gray: 2/5
Fraction of gray cars that are electrically powered: 2/3
(2/5) * (2/3) = 4/15
Therefore, 4/15 of the cars on the lot are both gray and electrically powered.
Simplify the expression: −3(−5y−6)−4
To simplify the expression −3(−5y−6)−4, you start by distributing the -3 across the terms inside the parentheses:
This gives: 3 * 5y + 3 * 6 - 4
Which simplifies to: 15y + 18 - 4
Finally, combining like terms, we get: 15y + 14
Therefore, the simplified expression is 15y + 14.
This gives: 3 * 5y + 3 * 6 - 4
Which simplifies to: 15y + 18 - 4
Finally, combining like terms, we get: 15y + 14
Therefore, the simplified expression is 15y + 14.